Perancangan Sistem Keamanan Aplikasi E-Voting Untuk Pemilihan Ketua Badan Eksekutif Mahasiswa Fakultas Teknik UISU Dengan Menggunakan Algoritma MD5 - Muhadi M.Ilyas Gultom; Darjat Saripurna (UIN Sumatera Utara, 2019)
E-voting Is the use of hardware and software to establish an electronic system that is useful in the electoral process by making electronic votes that replace ballot papers. E-Voting was introduced by several e-Government especially in Europe in a request to serve the voting provisions by providing a control system, so that voters can vote whenever and wherever. To avoid all forms of fraud and damage to data which is certainly very important for the voting process, it is necessary to secure data by applying cryptography to the data. Currently there are many methods or algorithms that can be used to protect data from various types of attacks, but of course each algorithm has advantages and disadvantages of each. MD5 is a concise message algorithm developed by Ron rivest. MD5 has actually been rooted in a series of concise message algorithms, which are the predecessors of md5, all developed by Rivest. The original digest message is called md.